Involvement of matrix metalloproteinases (MMP‐3 and MMP‐9) in the pathogenesis of irinotecan‐induced oral mucositis. (12th September 2014) - Al‐Azri, Abdul R.; Gibson, Rachel J.; Bowen, Joanne M.; Stringer, Andrea M.; Keefe, Dorothy M.; Logan, Richard M.
<x xml:space="preserve">Abstract</x> Objectives Matrix metalloproteinases (MMPs) are involved in both maintenance of healthy mucosa and mediation of several pathologies. Recently, MMPs and their inhibitors have attracted attention as potential mediators of mucositis. We investigated tissue expression of MMP‐3 and MMP‐9 over time in a pre‐clinical model of irinotecan‐induced oral mucositis (OM). Materials and methods Eighty‐one female Dark Agouti rats received either a single dose of irinotecan (200 mg/kg) or vehicle control. Rats were killed at different time points over a 72‐h period and tongue mucosa examined histologically. Tissue expression of MMP‐3 and MMP‐9 was characterized by standard qualitative immunohistochemistry. Results and discussion Epithelial thickness was reduced without any ulceration in the oral mucosa early after chemotherapy. Epithelial atrophy was associated with significant (P < 0.05) upregulation of MMP‐3 and MMP‐9 in all layers of the oral epithelium. The increase of MMP‐3 was also significant (P < 0.05) in lamina propria and submucosa. Most of changes in expression occurred early (1–6 h), coinciding with previously described upregulation of transcription factors and pro‐inflammatory cytokines in OM. Tissue expression of MMP‐3 and MMP‐9 followed different patterns of change over time, suggesting involvement in various aspects of OM pathophysiology. Conclusions These findings suggest vital roles played by MMP‐3 and MMP‐9 during OM pathophysiology. Further research is required to investigate the role of other MMPs and the naturally existing tissue inhibitors of MMPs. Research should also be directed to investigate beneficial effects of MMPs intervention therapies to prevent or reduce the severity of OM.